Clarinet Music from Russia and the Soviet Union 1917–1991: Discovering an Unexplored Side of the Clarinet Repertoire - Piirainen, Anne Elisabeth (Taideyliopiston Sibelius-Akatemia, DocMus-tohtorikoulu, 2021)
A large and stylistically diverse repertoire was composed for the clarinet in the former Soviet Union. However, few of these compositions are well known and regularly performed nowadays. This study explores the characteristics and variety of this specific repertoire from the point of view of a clarinetist. It aims to give insights on forgotten or unknown compositions and to reduce the research gap on this aspect of the clarinet repertoire. This study, carried out in the Sibelius Academy’s Arts study programme, consists of a series of five doctoral recital concerts and the thesis in the form of a website, including an extensive clarinet composition database. The thesis applies a variety of performance-based research methods. Part One of the thesis is dedicated to the series of concerts as well as their topics and program ideas. All concert programs were built entirely on music from the field of research, including works for clarinet solo and chamber music for clarinet, piano and strings. Part Two combines a historical contextualization of the repertoire with the performer´s perspectives on exemplary clarinet compositions from this period. The development of this part of the clarinet repertoire, examination of the artistic potential of selected works and her own performance observations are supported by video excerpts from the recital concerts. The material is subdivided into topics in chronological order, from the Russian Revolution until the dissolution of the Soviet Union. Special attention is given to clarinet works with elements from Jewish traditional music due to the particular use of the clarinet in these compositions. Part Three consists of a database of over five hundred works with clarinet from Russia and the Soviet Union in various instrumentations, gathered by the author from various sources, such as the composer´s work listings, catalogues and libraries. The database includes clarinet concertos and woodwind chamber music. A search function is added for the reader’s convenience. This study is meant as a starting point for a broader perception of clarinet music from Russia and the former Soviet Union among performers, audience and scholars.
Keywords: Venäjä; klarinetti; kamarimusiikki; esiintyminen; harjoittelu; DocMus